Gender equality and investments in adolescents in the rural Philippines - Bouis, Howarth E.; Palabrica-Costello, Marilou; Solon, Orville; Westbrook, M. Daniel; Limbo, Azucena B. (International Food Policy Research Institute, 1998)
...Many studies have looked at the way resources are distributed to men, women, and especially to small children, but one age group within the family has been largely ignored: the adolescents. Adolescence is a crucial period in that teenagers can make major contributions to their families’ welfare through their labor and earnings, in and outside the household, but may sacrifice their own wishes and future well-being in the process if such contributions come at the expense of investments in their education. The research methodology in this report, combining regression analysis with ethnography, provides a lesson in how complementarities between methodological approaches can be exploited...The research finds that parents are not unduly influenced by short-term needs and are ready to make substantial sacrifices in terms of current consumption in order to invest in their children’s future. The research also concludes that boys and girls in this rural area of the Philippines are generally treated equally, provid ing a contrast with other Asian settings where discrimination by gender is common. (Forward by Per Pinstrup- Andersen)